2010
DOI: 10.1097/mpg.0b013e3181df5b66
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Enteropathogens in Infants and Preschoolers With Acute Diarrhea in Western Mexico

Abstract: The present study estimates the prevalence of some enteropathogens in infants and preschoolers with acute diarrhea. From 2006 to 2007, 5459 consecutive stool samples were evaluated. Cryptosporidium parvum was the parasite identified with the higher frequency (5.1%), followed by Giardia lamblia (1.2%). Campylobacter jejuni was isolated in 858 cases (15.7%) and was the most frequent enteropathogen overall. The rates of C parvum, Shigella, and Salmonella were higher in the summer. Rotavirus had the expected winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
2
12
2
1
Order By: Relevance
“…In Mexico, C. jejuni was the most common cause of acute gastroenteritis in infants and preschoolers in 2006 and 2007 (isolated in 15.7% of 5,459 cases) (40). Campylobacteriosis is also very common in children in Guatemala, with incidence rates of 185.5 to 1,288.8 per 100,000 children (41).…”
Section: Epidemiologymentioning
confidence: 99%
“…In Mexico, C. jejuni was the most common cause of acute gastroenteritis in infants and preschoolers in 2006 and 2007 (isolated in 15.7% of 5,459 cases) (40). Campylobacteriosis is also very common in children in Guatemala, with incidence rates of 185.5 to 1,288.8 per 100,000 children (41).…”
Section: Epidemiologymentioning
confidence: 99%
“…This can be associated with food consumption in restaurants because the most common sources of infection are raw or undercooked meat, particularly poultry products. Contact with pets may cause infection, and outbreaks can be seen with the usage of untreated water and unpasteurized milk (11,12). As in our region, increasing temperatures are more suitable for the survival of Campylobacter.…”
Section: Discussionmentioning
confidence: 99%
“…C. jejuni (15.7%) was the most common enteropathogen in infants and preschoolers in Western Mexico in the study by Larrosa-Haro et al They reported higher summer rates of Salmonella spp., Shigella spp., and Campylobacter spp. (12).…”
Section: Discussionmentioning
confidence: 99%
“…Орґанізм людини також підпорядкований складній системі біоритмів -від короткотривалих на молекулярному рівні до багаторічних, зумовлених сонячною активністю. Циклічні варіації характерні не тільки для фізіолоґічних процесів, а й для захво рювань [9][10][11]. Один із найпоширеніших синдромів у педіатрії -стенозувальний ларин ґо трахеїт (СЛТ), у ґенезі якого провідна роль належить вірусам, також характеризується певними сезонними ритмами [5,6,8,13].…”
unclassified